REMOVE THE COPPER LAYER OF PCB BOARDS BY USING LASER ABLATION - Dunkins, Vitālijs; Martinovs, Andris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
The publication describes results of copper laser ablation which shows copper layer dependence of a laser radiation, such as supply, pulse frequency and processing speed reacts.